The Chinese trade ceramics found in Borneo – 11th century to 19th century - Asyaari Muhamad (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2021)
This paper focuses on the Chinese trade ceramic found in Borneo from the 11th century to the 19th century. In the years between 2005 and 2007, Baszley Bee Basrah Bee did joint research with the Museum of Sabah and The Department of Museums and Antiquity in the form of an archaeological survey at Pulau Bangi, Simpang Mengayau, Kudat in Sabah. In his survey, he discovered ceramics especially from the Song Dynasty (since 11th Century), Yuan Dynasty, Ming and Ch’ing Dynasty (from 14-19th century). In Brunei, archaeological sites such as at Sungai Limau Manis uncovered thousands of Song Dynasty ceramics. Nonetheless, proper documentation and research are still lacking. Hopefully, in the future, adequate documentation would further clarify our understanding of the ancient trade ceramics found in Borneo.